Income-carbon Emissions Nexus for Middle East and North Africa Countries: A Semi-parametric Approach - Awad, Atif; Abugamos, Hoda (International Journal of Energy Economics and Policy, 2017)
It is widely accepted that MENA region is significantly impacted by climate change. Evidence suggests that the region is positioned at the second place after North America in carbon emission. This study attempts to further examine the impacts of income on carbon emissions in MENA region through investigation of the existence of an environmental Kuznets curve (EKC). Within the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) framework, this is the first study in MENA region to explore the income-carbon emissions nexus; using panel data together with a semi-parametric panel fixed effects regression. Our data set is referred to a panel of 20 countries in MENA region spanning the period 1980 - 2014. With this information, we find evidence to support an inverted-U shaped relationship between income and CO2 emissions in the region. These findings suggest that environmental degradation may be reversible and environmental quality may be recoverable alongside the economic growth process in the region. Keywords: Per capita income, carbon emissions, STIRPAT environmental Kuznets curve, MENA region. JEL Classifications: Q01, Q28, Q52, Q51.